2007
DOI: 10.1089/oli.2007.0096
|View full text |Cite
|
Sign up to set email alerts
|

Modified 27-nt dsRNAs with Dramatically Enhanced Stability in Serum and Long-Term RNAi Activity

Abstract: The present study describes improved properties of 27-nt dsRNAs over 21-nt siRNAs, and accents on the possibility to use their modifications and conjugates for direct long-term gene silencing in viable cells and animals, avoiding conventional transfectants. Using a Renilla Luciferase gene-silencing system and cultured cell lines, we established that 27-nt dsRNAs possessed about three to five times higher "long-term" RNAi activity than 21-nt siRNAs and 21-nt dsRNAs. Moreover, if RNA duplexes were preincubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…No intact 21-mer siRNA is seen after 6 hours incubation in fetal calf serum. Consistent with earlier reports, the unmodified 27-mer duplexes were somewhat more nuclease resistant than 21-mer duplexes at the same site (Kubo et al, 2007), and small amounts of the unmodified 27-mer DsiRNA were still present at 6 hours. In contrast, an appreciable amount of the 2′OMe ASm modified 27-mer DsiRNA remained intact after 24 hours incubation in serum.…”
Section: Testing and Optimization Of Modification Patternssupporting
confidence: 91%
“…No intact 21-mer siRNA is seen after 6 hours incubation in fetal calf serum. Consistent with earlier reports, the unmodified 27-mer duplexes were somewhat more nuclease resistant than 21-mer duplexes at the same site (Kubo et al, 2007), and small amounts of the unmodified 27-mer DsiRNA were still present at 6 hours. In contrast, an appreciable amount of the 2′OMe ASm modified 27-mer DsiRNA remained intact after 24 hours incubation in serum.…”
Section: Testing and Optimization Of Modification Patternssupporting
confidence: 91%
“…It was found that bonds with 3′ pyrimidine nucleotides are cleaved faster than bonds with 3′ purines. Kubo and his colleagues demonstrated that degradation rate of dsiRNAs correlated with the amount of pyrimidines at the 3′ end [31]. At the same time, degradation rate of dsiRNAs also correlates with the presence of AU-rich domains that might be related to low thermal stability, easy dissociation, and faster cleavage by both endo-and exonucleases.…”
Section: Dicer Substrate Interfering Rnasmentioning
confidence: 98%
“…On the other hand, dsiRNAs with chemical modifications of the 5′ end possess high nuclease stability and RNAi activity in the cell-cultured medium. Thus, 5′-end amino-modified dsiRNA demonstrated improved RNAi activity and stability in the cell-cultured medium [31].…”
Section: Dicer Substrate Interfering Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The other approach utilize the inactivation of the sense strand of siRNA (for example, segmentation) to guarantee the incorporation of the antisense strand into activated RISC* independent from the thermodynamic properties of the duplex [99]. The silencing activity of siRNA can be increased by the lengthening of the duplex and converting siRNA into Dicer substrate DsiRNA [160,161] or by the modifications of the overhands affecting duplex thermodynamic asymmetry [162]. Single stranded analogs of siRNA can be also used as inducers of RNAi, in this case the problem of the strand selection does not exist [40,77].…”
Section: The Impact Of the Sirna Structure On The Efficiency Of Rnaimentioning
confidence: 99%